The poverty of work : selling servant, slave and temporary labor on the free market - Van Arsdale, David G. (Studies in critical social sciences ;, 2016)
In The Poverty of Work, Van Arsdale goes inside the world of temping and discovers a type of work dreadfully insecure yet growing rapidly. Furthermore, through a comprehensive historiography, he illustrates how employment agencies moved from England to North America during the colonial period, where they sold workers into many deprived employment statuses, including indentured servitude and slavery. Van Arsdale contends that had the history of employment agencies been better understood, they would have likely been abolished with slavery, or at the very least, more tightly controlled by government. Today, left largely unregulated, employment agencies are powerful corporations generating astonishing revenue by selling flexible, on-demand temporary workers. Unfortunately, this labor is trapping millions in a cycle of unemployment, despair, and poverty.